Loss of transforming growth factor β signalling in the intestine contributes to tissue injury in inflammatory bowel disease. Issue 2 (1st August 2001) - Hahm, K-B; Im, Y-H; Parks, T W; Park, S-H; Markowitz, S; Jung, H-Y; Green, J; Kim, S-J
Abstract : BACKGROUND: Inflammatory bowel disease (IBD) is a chronic inflammation of the gastrointestinal tract caused by an abnormal and uncontrolled immune response to one or more normally occurring gut constituents. AIM: Given the effects of transforming growth factor β1 (TGF-β1) on both the immune system and extracellular matrix, we postulated that alterations in TGF-β signalling in intestinal epithelial cells may play an important role in the development of IBD. METHODS: TGF-β signalling was inactivated in mouse intestine by expressing a dominant negative mutant form of the TGF-β type II receptor under the control of the mouse intestinal trefoil peptide (ITF)/TFF3 promoter. Transgenic mice (ITF-dnRII) developed spontaneous colitis presenting with diarrhoea, haematochezia, and anal prolapse when not maintained under specific pathogen free (SPF) conditions. Under SPF conditions we induced colitis by mixing dextran sodium sulphate (DSS) in drinking water to examine the significance of loss of TGF-β signalling in the pathogenesis of IBD. RESULTS: Transgenic mice showed increased susceptibility to DSS induced IBD, and elicited increased expression of major histocompatibility complex class II, generation of autoantibodies against intestinal goblet cells, and increased activity of matrix metalloproteinase in intestinal epithelial cells compared with wild-type littermates challenged with DSS. CONCLUSIONS: Deficiency of TGF-β signalling specifically in the intestine contributes to the development of IBD. Maintenance of TGF-β signalling may be important in regulating immune homeostasis in the intestine